A NEW MODEL OF PROFESSIONAL EDUCATION AS AN IMPERATIVE OF KNOWLEDGE-BASED ECONOMY - Sergey A. Filatov; Natalya G. Sukhorukova; Tatiyana N. Dudina (Moscow Polytechnic University, 2022)
This article analyzes the objective factors that cause the need for the new model of professional education in the conditions of the formation of knowledge-based economy. The socio-economic mechanism of transformation of the educational system in the post-industrial era is revealed. The experience of the university is presented.